Comparison of Kerta Desa Bali and Malaysian Indigenous Court - Karwiyah, Karwiyah; Judiasih, Sonny Dewi; Kusmayanti, Hazar (SASI, 2024)
Introduction: Customary courts are institutions of dispute resolution that are alive and well in customary societies. Indonesia, which is not much different from Malaysia, has a similar culture and has customary courts. Kerta desa Bali is one of Indonesia's customary courts at the village level and in Malaysia there are indigenous court.Purposes of the Research: This research paper will discuss the comparison of kerta desa Bali courts and Malaysian indigenous court.Methods of the Research: This research uses a normative juridical approach. The research specification is descriptive analytical, namely by describing and comparing of kerta desa Bali and Malaysian indigenous court which are associated with regulations, legal theories, and community customs. The research stages use primary, secondary, and tertiary legal materials with data collection methods carried out through literature studies.Results of the Research: Kerta desa Bali sought to resolve disputes through deliberation and peace, although customary courts were not included in the judicial system, but did not absolutely reject dispute resolution mechanisms through customary courts. Meanwhile, Malaysia emphasizes that there are three judicial systems, namely district courts, sharia courts, and indigenous courts in Sabah and Sarawak, which have structures and according to the customs of the indigenous population.